Freelancers, Self-Employment and the Insurance against Social Risks - Fachinger, Uwe; Frankus, Anna (Senate Hall, 2015)
In contrast to dependent employees, most self-employed people are free to choose if they wish to insure themselves against social risks such as longevity, illness, or long term care. Alongside the general protection scheme, which provides security at a minimal level, self-employed people are not or are only partially covered by statutory systems. And even in case of coverage, statutory social security provisions for self-employed persons vary greatly. Un-fortunately, we know very little about the situation of self-employed people regarding the protection against social risks, as reliable data are missing. Therefore the state of knowledge is far from satisfying. However, the few available findings indicate that large groups are not covered at all. Against the background of the upsurge of these professions, this lack of coverage is indicative of an increasingly precarious position or social exclusion of those groups. Keywords: social risks, insurance, social security, self-employment, independent professionals
Keywords: social risks|insurance|social security|self-employment|independent professionals